Knowledge Relationships Mother With Temper Tantrum Behavior In Children In Puskesmas Payung Sekaki Pekanbaru 2019: Knowledge Relationships Mother With Temper Tantrum Behavior In Children In Puskesmas Payung Sekaki Pekanbaru 2019 - Berliana Irianti (Journal of Midwifery and Nursing, 2020)
Knowledge is what is known by the person or respondents with respect to healthy and sick or health. Temper tantrums are an outburst of explosive and uncontrolled. Temper tantrums often occur in children aged 15 months to 6 years. Children's early period was the golden era for parents, children's early period is a difficult time for most of the child's personality development fraught with difficulties and children are often demanding freedom despite their liberty still fail to obtain. This study aims to determine the "Knowledge Capital Relationship With Temper Tantrum Behavior In Children In Puskesmas Umbrella Sekaki 2019". This research is quantitative analytic design by using Cross Sectional. Held on March to March 2019 in the working area of ??Puskesmas Umbrella Sekaki Year 2019. Total population of 8444 people and a total sample of 99 people with the sampling technique accidental sampling. Instrument of this research using questionnaires, data processing univariate presented in the form of a frequency distribution table followed by a bivariate analysis using SPSS vs. 20, then presented descriptively and analytically through statistical tests. The survey results revealed that the majority of women are knowledgeable enough as many as 72 respondents (72.7%) with children do not have temper tantrums as many as 76 children (76.8%). From the results of the chi square test showed that the P value (0389)> ? (0:05)